The integrity gap : Canada's environmental policy and institutions - Lee, Eugene E., 1924-; Perl, Anthony, 1962- (University of British Columbia Press ; Eurospan, 2003)
This thoughtful collection exposes the gap between rhetoric and performance in Canada's response to environmental challenges. Canadians, despite their national penchant for environmental discussion, have fallen behind their G-8 peers in both domestic commitments and international actions. In a cogent examination of the issue, eight authors demonstrate how Canada's configuration of political and economic institutions has limited effective environmental policy. Canadian environmental institutions, the authors argue, have produced an integrity gap: the sustainability rhetoric adopted by policymakers fails to achieve concrete results. In an analysis that penetrates several policy domains and combines various disciplinary, sectoral, and geographic perspectives, the authors demonstrate how Canada fell from leader to laggard within the international environmental community. Placing the study of Canadian environmental policy within a sound theoretical framework for the first time, this book makes a significant contribution to existing policy scholarship. It will find an enthusiastic audience among political scientists, neo-institutional theorists, policy analysts, and students at both undergraduate and graduate levels.